2016
DOI: 10.1111/acps.12572
|View full text |Cite
|
Sign up to set email alerts
|

Placebo‐controlled pilot trial testing dose titration and intravenous, intramuscular and subcutaneous routes for ketamine in depression

Abstract: Antidepressant response occurred at a range of doses and at <0.5 mg/kg. The dose-titration approach is a practical method for optimizing the efficacy - side-effects trade-off on an individual patient basis. This pilot study provides preliminary evidence for SC injection as a practical, feasible and efficacious treatment approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
182
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(195 citation statements)
references
References 24 publications
8
182
0
5
Order By: Relevance
“…In addition, we found that patients with melancholic or melancholic–anxious depression took longer to achieve response/remission than those with anxious or no subtype depression. This relatively increased remission time might have large implications since the rapid antidepressant effect of single ketamine has been validated, but no agreement of the regimen for repeated‐dose ketamine treatment has been reached .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that patients with melancholic or melancholic–anxious depression took longer to achieve response/remission than those with anxious or no subtype depression. This relatively increased remission time might have large implications since the rapid antidepressant effect of single ketamine has been validated, but no agreement of the regimen for repeated‐dose ketamine treatment has been reached .…”
Section: Discussionmentioning
confidence: 99%
“…Twelve patients who received ketamine achieved response and met remission criteria at doses as low as 0.1 mg/kg regardless of route of administration. Indeed, all three routes of ketamine administration resulted in comparable antidepressant effects in a dose-related fashion, with the fewest adverse effects seen via the subcutaneous route [77]. Larger sample dose optimization studies are actively being conducted (NCT01558063).…”
Section: Ketamine As a Prototypic Glutamatergic Antidepressant Agentmentioning
confidence: 99%
“…In this case series, 20 of 26 (77%) patients with bipolar depression or MDD who received sublingual racemic ketamine every two to three days or weekly reported improved and stable mood, cognition, and sleep with only mild and transient light-headedness as a common side effect (no euphoria, psychotic, or dissociative symptoms). In a small, placebo-controlled, crossover trial, subcutaneous and intramuscular injections of subanesthetic-dose ketamine were found to be associated with antidepressant response in a similar fashion to IV ketamine administrations; in that study, subcutaneous injection was associated with the fewest adverse effects [77]. Clearly, replication of both findings through larger randomized clinical trials is warranted.…”
Section: Ketamine As a Prototypic Glutamatergic Antidepressant Agentmentioning
confidence: 99%
“…Recently, Loo et al 24 assessed the assessed the feasibility, efficacy and safety of intravenous ( n =4), intramuscular ( n =5) and subcutaneous ( n =6) routes for treating depression with ketamine (versus midazolam active comparator) in treatment-resistant depression patients. Doses were also titrated from 0.1 mg kg −1 up to 0.5 mg kg −1 in separate treatment sessions separated by at least 1 week.…”
Section: Experimental Treatments For Depressionmentioning
confidence: 99%